Pro-environmental behaviour among primary students through non-formal activities - a case study in Pulau Selakan, Semporna, Sabah - Wong, Charmaine Andrea; Mohammad Afandi, Syamsul Herman; Ramachandran, Sridar; Shuib, Ahmad (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Environmental Education within the Malaysian formal education system has evolved in the last thirty years and is now integrated into every subject in local schools. However, NGOs and educators have highlighted the need to educate young children on environmental issues. This is due to the fact that there seems to be a gap between what has been advocated, and the actual practices in schools and other educational institutions. In Semporna, despite the efforts of the local government and non-profit organizations in educating locals on sustainable environmental practices, scholars still report that sustaining the tourism industry may be a problem if major environmental aspects are not looked into. Recent research has indicated that environmental activists and educators have attributed their active involvement in this field due to two main factors which are: their formative childhood experiences and from having positive role models in their childhood years. This research aims to use the constructivism theory to create non-formal educational activities that are applicable to the lives of primary one to primary three students at Pulau Selakan, Semporna. Using the Constructivist Design Model, activities will be developed and carried out regularly within a three month period. After which, learning would be assessed through authentic assessment methods, based on the given theory. If the results of these activities show that students have learned to understand and solve environmental problems more effectively and confidently, this would have implications for the environmental educators seeking to introduce pro-environmental behaviour to children.